Bioconversion of Coffee Fruit Bark Waste into Commercially Valued, Healthy, and High-Quality Compost Fertilizer as a Solution for Community Economic Independence and Environmental Sustainability - Fahrul Rozi Maulana; Reswita Reswita; Samsul Bahri; Ahmad Faris; M. Habib Mushlih; Ahmad Ansori; Budi Chaknur; Janna Alvina (Universitas Muhammadiyah Palembang, 2024)
Coffee is one of the plantation commodities in Indonesia which has quite high economic value among other plantation commodities such as cocoa and tea. Ulubelu District is one of the largest coffee producing areas in Lampung Province with a land area of 7,549 hectares with a production capacity of 4,970 tons/year which has the potential to produce 7.8 tons/year of coffee fruit skin waste. So there is a need for a solution to process coffee fruit skin waste into a product that has sales value and use value for the community. The aim of this community service activity is as an alternative to increasing community knowledge and skills in utilizing local potential into local products. The method applied in this service is to carry out several stages such as pre-activity, outreach, implementation and evaluation of activities. The result of carrying out this service activity is an increase in the community's knowledge and skills in utilizing and processing the potential of coffee fruit skin waste into healthy and quality compost. Apart from that, the aim of carrying out this service is to create a new business community so that it can improve community welfare from the community's ability to utilize local potential into local products that have marketable value.